1994
DOI: 10.1056/nejm199412013312203
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor in Ocular Fluid of Patients with Diabetic Retinopathy and Other Retinal Disorders

Abstract: Our data suggest that VEGF plays a major part in mediating active intraocular neovascularization in patients with ischemic retinal diseases, such as diabetic retinopathy and retinal-vein occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

51
1,735
9
48

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,388 publications
(1,843 citation statements)
references
References 28 publications
51
1,735
9
48
Order By: Relevance
“…RT-PCR and Western blot analysis indicated that VEGF-B was expressed by seven of seven CRC cell lines utilized in this study (not shown), suggesting that VEGF ligands may be involved in an autocrine loop activating VEGFR-1. PlGF, which also acts as a ligand for VEGFR-1 (Aiello et al, 1994), was also expressed by two of seven of the CRC cell lines tested (RT-PCR data not shown) and hence may be implicated as well. Although our studies demonstrate a role for VEGFR-1 in steps involved in tumor progression and metastasis, it is unknown what role neuropilin-1 (NRP-1) plays in modifying these effects.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR and Western blot analysis indicated that VEGF-B was expressed by seven of seven CRC cell lines utilized in this study (not shown), suggesting that VEGF ligands may be involved in an autocrine loop activating VEGFR-1. PlGF, which also acts as a ligand for VEGFR-1 (Aiello et al, 1994), was also expressed by two of seven of the CRC cell lines tested (RT-PCR data not shown) and hence may be implicated as well. Although our studies demonstrate a role for VEGFR-1 in steps involved in tumor progression and metastasis, it is unknown what role neuropilin-1 (NRP-1) plays in modifying these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Wautier et al (44) reported that infusion of diabetic red blood cells into normal rats can induce vascular hyperpermeability, which was completely inhibited by anti-RAGE IgG; they also demonstrated that an antioxidant, probucol, can similarly reverse the red blood cell transfer-induced vascular permeability, suggesting a role of AGE-RAGE interactions and the involvement of an oxidant stress-sensitive pathway in the development of hyperpermeability. Recent clinical studies at different institutions have established that intraocular concentrations of VEGF correlated with active neovascularization (45,46). Further, the increased permeability of retinal capillaries and the breakdown of the blood-retinal barrier have been shown to be as an early event in both human diabetic subjects and streptozotocin diabetic rats followed by new vessel formation (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…This protein, vascular endothelial cell growth factor (VEGF), has been implicated in the stimulation of normal angiogenesis and the increased capillary formation that characterizes proliferative diabetic retinopathy (5). VEGF is also considered to be critical for the angiogenesis that underlies tumor metastasis (6,7).…”
mentioning
confidence: 99%